Frequency of Low Birth Weight Babies in Patients with Short Inter-Pregnancy Interval - Jatoi, Sheeba; Jahan Ara Hassan (Indus Journal of Bioscience Research, 2025)
Objectives: To determine the frequency of low birth weight babies in patients with short inter-pregnancy interval. Study type: cross sectional study. Settings: Department of Obs & Gynae, Dow International Medical College, DUHS Ojha Campus, Karachi. Duration of study: 25th February 2025 to 24th May 2025. Methodology: A total of 163 women in the age range of 18 to 40 years, with a gestational age of 37 to 41 weeks, and with a short inter-pregnancy interval were included. Diabetes mellitus (FBS >110 mg/dl on two consecutive occasions), pre-eclampsia (B.P >130/90 mmHg and proteinuria on dipstick), hepatic dysfunction and heart disease (s/bilirubin >1 mg/dl), severe intrauterine growth retardation (determined by ultrasonography), antepartum hemorrhage, and h/o chronic hypertension were all excluded. Patients were assured of their anonymity and gave their informed agreement before their data was used in study. Next, the following were recorded: age, gestational age, parity, height, weight, BMI, anemia (yes/no), location of residence (rural/urban), and monthly income (<20000/20000-40000/40000). Low birth weight babies (yes/no) weighing less than 2.5 kg were observed in all moms. Results: The study’s participants ranged in age from 18 to 40 years, with a mean age of 28.54 ± 5.93 years. Mean gestational age was 38.43 ± 1.52 weeks. Mean BMI was 29.43 ± 4.51 kg/m2. 18 (11.04%) patients with short inter-pregnancy interval had low birth weight babies. Conclusion: It is determined that a short period between pregnancies might considerably result in low birth weight, which can be prevented by extending the time between pregnancies. This can be accomplished by advising people to use effective contraception.